Pengaruh Desain Website, Harga Dan Rating Terhadap Keputusan Pembelian Di Market Place Lazada (Studi Kasus Pada Masyarakat Jalan Garu III Harjosari I Kecamatan Medan Amplas) - Yudistian, Ananda Yudi; Tukimin, Tukimin (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
This study aims to analyze the influence of website design, price, and ratings on purchasing decisions in the Lazada Marketplace. The research adopts a descriptive quantitative method with respondents from the Jalan Garu III community, Harjosari I, Medan Amplas District, who shop online via Lazada. Data analysis employs multiple linear regression to identify the effect of each independent variable on purchasing decisions. The results reveal that website design, price, and ratings significantly influence purchasing decisions, both partially and simultaneously. These findings indicate that these factors are key considerations for consumers when selecting products on e-commerce platforms. The study concludes that optimizing website design, offering competitive pricing, and maintaining good product ratings can enhance consumer purchasing decisions. This research is expected to provide practical insights for e-commerce players to improve competitiveness by enhancing service quality.